2015
DOI: 10.1002/oca.2189
|View full text |Cite
|
Sign up to set email alerts
|

A feasibility study of sliding mode predictive control for greenhouses

Abstract: Summary In this work, the feasibility of applying a Sliding Mode Predictive Controller (SMPC) to improve greenhouse inside air temperature control is addressed in terms of energy consumption, disturbance handling and set point tracking accuracy. Major research issues addressed concern the SMPC robustness study in greenhouse control, as well as to evaluate if the levels of performance and energy consumptions are acceptable when compared with the traditional generalized predictive controller. Besides the externa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 30 publications
(41 reference statements)
0
4
0
Order By: Relevance
“…In the greenhouse context, many authors have suggested the adoption of MPC schemes to control climate environment in greenhouses, whereas, few papers have considered implementations of microgrids in agriculture, as well as networks of greenhouses. The authors of [110] investigated the possibility of considering an MPC to increase greenhouse indoor air temperature control. The design of a predictive control model using switch actuators as heater and ventilation windows to control greenhouse temperature has been investigated in [111].…”
mentioning
confidence: 99%
“…In the greenhouse context, many authors have suggested the adoption of MPC schemes to control climate environment in greenhouses, whereas, few papers have considered implementations of microgrids in agriculture, as well as networks of greenhouses. The authors of [110] investigated the possibility of considering an MPC to increase greenhouse indoor air temperature control. The design of a predictive control model using switch actuators as heater and ventilation windows to control greenhouse temperature has been investigated in [111].…”
mentioning
confidence: 99%
“…Because the switching frequency of the SMC is reduced in the SMPC method, it is used to reduce the vibration experienced by a cantilevered aluminum beam in [116]. The SMPC is applied to improve greenhouse inside air temperature control in [117]. The SMPC is also applied to heat exchangers and other temperature systems [118], [119].…”
Section: A Application In Process Systemsmentioning
confidence: 99%
“…The PID controller starts by reading sensor values, then it computes the corresponding actuator output by adjusting proportional, integral, and derivative factors [43]. Adjusting PID controller factors can be achieved using different approaches [44].…”
Section: Figure 5 Greenhouse Closed Loop Temperature Regulation Systemmentioning
confidence: 99%